To find the values of x that make the equation `\left(x-3\right)\left(x+5\right)=0` equal to zero, we need to solve for x in the equation.
This equation can be rewritten as a product of two factors, `(x - 3)` and `(x + 5)`, that equal zero:
`(x - 3)(x + 5) = 0`
To set each factor equal to zero and solve for x, we have two separate equations:
x - 3 = 0
x + 5 = 0
For the first equation, by adding 3 to both sides, we get:
x = 3
For the second equation, by subtracting 5 from both sides, we get:
x = -5
Therefore, the values of x that make the equation equal zero are x = 3 and x = -5.
Find the values of x that make the following equation equal zero:
`\left(x-3\right)\left(x+5\right)=0`
1 answer